A new azafluorenone from the roots of Polyalthia cerasoides and its biological activity - Pumsalid K. (2014)
Chromatographic separation of the ethyl acetate extract of roots of Polyalthia cerasoides has led to the isolation of the new compound, 6,8-dihydroxy-7-methoxy-1-methyl-azafluorenone. This compound exhibited potent cytotoxic activities with IC50 values in the range of 2.64-3.58 μg.mL-1 for A549, GLC4 and GLC4/Adr cells, but was not recognized by ABCC1/MRP1 protein. The compound also showed very strong inhibition of M. tuberculosis using a broth microdilution method, with an MIC value of 0.78 μg.mL-1, which was equal to that of ofloxacin, one of the four antibiotic drugs used as a positive control.